Cervical HPV infection in Yueyang, China: a cross-sectional study of 125,604 women from 2019 to 2022 - Hou, Jinfeng; Zeng, Min; Liu, Chongmei; Xie, Bochao; Li, Yu; Wu, Longyun; Zhu, Long; Li, Manqiu; Zhang, Zhihui; Zhang, Xiaoyun; Ge, Yangqing (Frontiers in Public Health, 2023)
Objective: Human papillomavirus (HPV) infection is currently the main cause of cervical cancer and precancerous lesions in women. The aim of this study was to investigate the epidemiological characteristics of HPV genotypes among women in Yueyang city and to provide a basis for the prevention and treatment of cervical cancer in this city. Methods: A cross-sectional study was conducted on 125,604 women who had received treatment from eight hospitals in Yueyang city from September 2019 to September 2022. Analysis of the prevalence of HPV in patients. Results: The prevalence of HPV was 20.5%（95%CI: 20.2-20.7%）, of which the high-risk type (HR-HPV) accounted for 17.5%（95%CI: 17.3-17.7%）and the low-risk type (LR-HPV) accounted for 5.0%（95%CI: 4.9-5.1%）. Among the HR-HPV subtypes, the top five in prevalence, from the highest to the lowest, were HPV52 (5.1%), HPV16(2.7%), HPV58 (2.6%), HPV53 (2.4%), and HPV51 (1.7%). The main LR-HPV infection types were HPV81 (2,676 cases, OR=2.1%; 95%CI, 2.0-2.1%). Among the infected patients, 19203 cases (OR=74.3%; 95%CI, 73.8-74.9%）had a single subtype, 4673 cases (OR=18.1%; 95%CI, 17.6-18.6%）had two subtypes, and 1957 cases (OR=7.6%; 95%CI, 7.3-7.9%）had three or more subtypes. HPV prevalence is highest among women <25 years, 55–64 years and ≥65 years of age. Conclusion: The prevalence of HPV in women in Yueyang city was 20.5%, with HR-HPV being dominant. As women aged <25 years, 55–64 years, and ≥65 years are at a relatively higher risk, more attention should be paid to them for prevention and control of HPV infections.